AN ANALYTICAL REVIEW OF THE IMPLEMENTATION OF GOODS AND SERVICES TAX IN UTTAR PRADESH: FISCAL TRANSFORMATION AND ECONOMIC REORDERING - Singh, Dhananjay Kumar; Singh, Binod Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Prior to the introduction of the Goods and Services Tax (GST) in 2017, India had a complex and inefficient system of indirect taxation. States such as Uttar Pradesh depended on a pile of levies, including VAT, CST, entry tax, octroi, and entertainment tax. Each had its own rates, exemptions, and enforcement mechanisms. That translated into having to pay more than one tax on a good and wade through a bureaucratic maze made national in scope. Octroi and entry taxes resulted in long waits for the transporters on UP's highways, causing a loss of money and increasing the cost of doing business. Larger ones are fully informal to be taxed and not to be taxed, encouraging direct formalization. Small businesses in rural areas are either in full informality to opt not to be taxed or directly encourage formality.